Search frictions, financial frictions and labour market fluctuations in emerging markets - Sumru Altug; Serdar Kabaca (Bank of Canada, 2014)
This paper examines the role of the extensive and intensive margins of labour input in the context of a business cycle model with a financial friction. We document significant variation in the hours worked per worker for many emerging-market economies. Both employment and hours worked per worker are positively correlated with each other and with output. We show that a search-theoretic context in a small open-economy model requires a small income effect to explain these regularities at the expense of a smaller wage response. On the other hand, introducing a financial friction in the form of a working capital requirement can explain the observed movements of labour market variables such as employment and hours worked per worker, as well as other distinguishable business cycle characteristics of emerging economies. These include highly volatile and cyclical real wages, labour share, and consumption. – – Dans cette étude, les auteurs se penchent sur le rôle joué par les marges extensive et intensive du travail dans le cadre d'un modèle du cycle économique incorporant une friction financière. Ils mettent en évidence des variations significatives des heures travaillées par ouvrier parmi de nombreux marchés émergents. Ils constatent, en outre, que l'emploi et les heures travaillées par ouvrier sont corrélés positivement entre eux, de même qu'avec la production. Ils montrent qu'un modèle intégrant des frictions d'appariement sur le marché du travail dans une petite économie ouverte ne peut expliquer ces régularités que lorsque l'effet de revenu est modéré, impliquant une faible réaction des salaires. Par ailleurs, l'introduction d'une friction financière, sous la forme d'exigences de fonds de roulement, permet au modèle d'expliquer les mouvements observés de variables du marché du travail comme l'emploi et les heures travaillées par ouvrier, ainsi que d'autres aspects particuliers du cycle économique dans les economies émergentes, tels que la cyclicité et la forte volatilité des salaires réels, de la part du travail et de la consommation.
Keywords: F41; E44; J40; 330; Business fluctuations and cycles; Labour markets; Development economics; International topics; Interest rates